Polymeric Nanocapsules for Vaccine Delivery: Influence of the Polymeric Shell on the Interaction With the Immune System - Peleteiro, Mercedes; Presas, Elena; González-Aramundiz, Jose Vicente; Sánchez-Correa, Beatriz; Simón-Vázquez, Rosana; Csaba, Noemi; Alonso, María J.; González-Fernández, África (Frontiers in Immunology, 2018)
The use of biomaterials and nanosystems in antigen delivery has played a major role in the development of novel vaccine formulations in the last few decades. In an effort to gain a deeper understanding of the interactions between these systems and immunocompetent cells, we describe here a systematic in vitro and in vivo study on three types of polymeric nanocapsules (NCs). These carriers, which contained Protamine (PR), Polyarginine (PARG) or Chitosan (CS) in the external shell, and their corresponding nanoemulsion were prepared and their main physicochemical properties were characterized. The particles had a mean particle size in the range 250–450 nm and a positive zeta potential (~ 30–40 mV). The interactions of the nanosystems with different components of the immune system were investigated by measuring cellular uptake, reactive oxygen species production, activation of the complement cascade, cytokine secretion profile, and MAP kinases/NFκB activation. The results of these in vitro cell experiments showed that the nanocapsule formulations that included the arginine-rich polymers (PR and PARG) showed a superior ability to trigger different immune processes. Considering this finding, PR and PARG NCs were selected to assess the association of Hepatitis B antigen (rHBsAg) as a model and to evaluate their ability to produce a protective immune response in mice. In this case, the results showed that PR NCs elicited higher IgG levels than PARG NCs and that this IgG response was a combination of anti-rHBsAg IgG1/IgG2a. This work highlights the potential of PR NCs for antigen delivery as an alternative to other positively charged nanocarriers.